Criticality of metals for electrochemical energy storage systems – Development towards a technology specific indicator. Issue 3 (20th March 2014) - Simon, B.; Ziemann, S.; Weil, M.
Abstract : The technology of electrochemical energy storage (EES) is supposed to play a key role in the near future for mobility systems characterized by electric vehicles as well as for stationary applications providing energy supply as they represent the interface between transport and energy networks. The performance of EES systems is closely linked to the applied battery materials which contain metals often considered critical. For determining criticality of metals different approaches have been used which however evaluate such materials for the economy as a whole. What has been missing up till now is the examination of critical raw materials for individual technologies.Therefore it is intended to develop a technology specific criticality indicator for battery materials.The focus of this paper is developing a method to indicate the significance of raw materials for electrochemical active materials used by lithium-ion batteries (LIB) which are currently very promising EES for mobile and stationary applications. In order to implement this at first the following three aspects were analyzed and put in relation to each other: importance of electrode materials, amount of metal in the active material and exploitable metal reserves. The combination of these factors resulted in a relevance index (RI) which allows determining the relevance of raw materials in different types of LIBs. Based on this index the development of a technology specific criticality indicator has to integrate further aspects being the focus of future work.